Emerging Plasma Technology That Alleviates Crop Stress During the Early Growth Stages of Plants: A Review - Song, Jong-Seok; Kim, Seong Bong; Ryu, Seungmin; Oh, Jaesung; Kim, Do-Soon (Frontiers in Plant Science, 2020)
Crops during their early growth stages are vulnerable to a wide range of environmental stressors; thus, earlier seed invigoration and seedling establishment are essential in crop production. As an alternative to synthetic chemical treatments, plasma technology could be one of the emerging technologies to enhance seed germination and seedling vigor by managing environmental stressors. Recent studies have shown its beneficial effects in various stress conditions, suggesting that plasma treatment can be used for early crop stress management. This paper reviewed the effects of different types of plasma treatments on plant responses in terms of the seed surface environment (seed scarification and pathogen inactivation) and physiological processes (an enhanced antioxidant system and activated defense response) during the early growth stages of plants. As a result, plasma treatment can enhance seed invigoration and seedling establishment by alleviating the adverse effects of environmental stressors such as drought, salinity, and pathogen infection. More information on plasma applications and their mechanisms against a broad range of stressors is required to establish a better plasma technology for early crop stress management.